Effect of larval handling on black soldier fly life history traits and bioconversion efficiency - Loiotine, Zaira; Gasco, Laura; Biasato, Ilaria; Resconi, Andrea; Bellezza Oddon, Sara (Frontiers in Veterinary Science, 2024)
The black soldier fly is considered the most promising insect species for mass production; however, information on the effects of handling, which is unavoidable during experimental trials and rearing practices, is still limited. To address this gap, three different manipulation intensities were tested on 100 6-day-old larvae per replica (6 replicates/treatments) fed on Gainesville diet: (1) hard-handled (HH), larvae underwent continuous manipulation until the end of larval stage, (2) soft-handled (SH), larvae were manipulated after the appearance of the first prepupa, (3) no-handled (NH), larvae remained untouched. Every 4 days from the beginning to the end of the larval stage, the manipulations lasted 30 minutes and occurred under laboratory conditions (20°C). During the sampling operations, at least 30 larvae were randomly extracted, washed, dried, and weight-mimicked. At the end of larval stage, all the boxes remained untouched until the adult fly stage, and the emergency rate and sex ratio were evaluated on dead flies. Data were statistically analyzed using IBM SPSS V20.0.0 software and the considered significance level was p < 0.05. The larval stage lasted 8.2 days for both HH and SH (p > 0.05). Despite the HH larvae being the most manipulated, no difference was also observed in final weight (HH, 160 mg; SH, 150 mg -p > 0.05) and survival rate (HH, 96.2%; SH, 94.5% -p > 0.05). The manipulation did not influence the bioconversion capacity of the larvae (bioconversion efficiency corrected for the residue: HH, 14.3%; SH, 12.91%; reduction rate: HH, 58.4%; SH, 55.9%; waste reduction index: HH, 7.28%/day; SH, 7.25%/day; p > 0.05). Finally, the development time from larva to fly (about 20.7; p>0.05), the emergency rate (NH: 92.8%; SH: 89.5%; HH: 82.7%) and sex ratio (~1.2% to male flies) were not affected by the handling (p>0.05).In conclusion, the handling procedures used in the current study did not influence the life history traits of the black soldier fly. However, further studies are needed to evaluate if different experimental protocols on various scales, the colony strain or other handling procedures may suggest a different scenario or confirm the results.